Mapping the Development of Social Policy in Indonesia: Analysis of Research Trends and Dominant Concepts - Rizky Perdana, Gusti Naufal (Universitas Negeri Gorontalo, 2025)
Discussion on social policy has become an important focus in both academic and practical realms, especially in the context of the ever-changing social dynamics in society. This research applies bibliometric analysis to explore trends and concepts related to social policy in Indonesia from 2013 to 2023. Utilizing data from Scopus, the study identifies the evolution, patterns, and dominant issues in the literature on social policy. The results indicate a significant increase in the number of publications since 2017, highlighting a growing interest in the field of social policy in Indonesia. The analysis also reveals contributions from leading authors, institutions, countries, document types, and subjects related to social policy. Furthermore, the findings highlight the most cited articles and identify dominant concepts in social policy research in Indonesia, such as decommodification, disability, COVID-19, and welfare regime change. This research provides in-depth insights into the advancements in social policy research in Indonesia and outlines directions for future research.